Glutaredoxin 5 as a novel target for β cell survival and regeneration - Zhou, Mengmeng; Justus Liebig University Giessen (My University, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by progressive pancreatic β cell dysfunction and insulin resistance, ultimately leading to persistent hyperglycemia and severe systemic complications. Increasing evidence suggests that mitochondrial dysfunction, iron imbalance, and lipid overload contribute to β cell failure. Glutaredoxin 5 (Grx5), a mitochondrial protein involved in iron-sulfur cluster biogenesis, plays an important role in cellular iron homeostasis. However, its function in pancreatic β cells under lipotoxic conditions remains unclear. This thesis investigated the role of Grx5 in β cell survival and function, focusing on its interaction with free fatty acids and iron metabolism. In vitro experiments were performed using mouse MIN6 cells and human EndoC-βH3 cells. Cells were exposed to oleic acid or treated with ferroptosis modulators, and metabolic activity, insulin secretion, lipid peroxidation, and iron homeostasis were analyzed. In addition, Grx5 expression was knocked down by siRNA to assess its functional role in β cells. In vivo, β-cell-specific Grx5-overexpressing mice were subjected to a high-fat diet to evaluate glucose metabolism. Furthermore, EndoC-βH3-derived pseudoislets were transplanted into streptozotocin-induced diabetic mice to assess their therapeutic potential. The results showed that oleic acid treatment in β cells led to reduced metabolic activity, insulin content, and secretion, accompanied by increased mitochondrial iron accumulation and decreased levels of Grx5 and Gpx4. In addition, the ferroptosis inducer ML-162 reduced insulin content and secretion, Grx5 levels, and increased lipid peroxidation and mitochondrial free iron accumulation. Cell metabolic activity was only reduced in the presence of oleic acid, and the reduction of Gpx4 and mitochondrial iron accumulation was more evident in the presence of oleic acid. Notably, the ferroptosis inhibitor Liproxstatin-1 was able to alleviate the oleic acid-induced reduction in insulin and Grx5 levels, as well as the associated lipid peroxidation and mitochondrial free iron overload. This suggests that exposure to oleic acid increases susceptibility to ferroptosis, an iron-dependent form of cell death characterized by lipid peroxidation. Grx5 knockdown resulted in reduced insulin content and secretion, increased lipid peroxidation, and mitochondrial free iron overload. This was accompanied by cytoplas mic free iron depletion and decreased cell metabolic activity. However, Grx5 overexpression in vivo did not significantly protect against high-fat diet-induced hyperglycemia, suggesting a limited systemic effect. Finally, EndoC-βH3 pseudoislets demonstrated enhanced glucose-stimulated insulin secretion and improved glycemic control after transplantation, although differences compared to native islets indicate potential functional limitations. In conclusion, we propose that exposure to oleic acid leads to decreased Grx5 levels, impairing iron metabolism, promoting lipid peroxidation, and eventually causing β cell dysfunction. However, Grx5 overexpression in vivo fails to reverse high fat diet-in duced hyperglycemia. Additionally, we highlighted the potential of pseudoislet trans plantation as a therapeutic strategy for diabetes.
Keywords: ddc:610; ddc:570